Effect of rainfall on surface reaeration - Wickramanayake, G. Bandula; Banks, Robert B.; Lohani, Bindu N.; Nguyen, Cong Thanh; The Royal Danish Government (Bangkok : Asian Institute of Technology, 1979)
In the present research, experiments have been carried out to study the effect of rainfall on surface reaeration. A statistical analysis of the experimental results has shown that the oxygen transfer coefficient due to rain is directly proportional to the power of the rainfall. In addition, an expression to evaluate the oxygen transfer coefficient, both due to rainfall and mechanical mixing has also been developed. By considering the relationship between the power of a rainfall and rainfall intensity, the empirical formula is modified to correlate the oxygen transfer coefficient and rainfall intensity for natural rains. The experimental results, along with the established relationships, give rise to the conclusion that the transfer coefficient due to the combined effects of rain and mechanical agitation is less than the sum of the transfer coefficients due to the two effects considered separately. The results obtained in this study further explain that the addition of oxygen from oxygen saturated raindrops is an important factor in studies related to surface reaeration.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1979
Keywords: Rain and rainfall